The Parenting Training Model Based On Spiritual Intellegence To Improve The Mother To Child Care In The Family - Ilham, Asni (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
The main problem of this research is the low level of maternal care in the family. This is probably caused by the limited frequencies of the maternal participation in the parenting training programs. In response to this phenomenon required an effort to empower the mother by giving them the knowledge and skills necessary to implement good parenting. Women empowerment program implemented through training. In this study will be implemented the parenting training model based on spiritual intelligence, which is alleged to be effective for improving motherâs behavior in family child care. The theoretical foundation of this research is the concept of parenting training model, adult education concept, the child family care, the spiritual intelligence concept, and the concept of early childhood education.The method that used in this study was a quasi-experimental. The design is the design (pretest -posttest) a group (the one group pretest-posttest design). Groups of subjects were mothers of young children in early childhood Almourky Gorontalo district, amounting to 30 people. The techniques of data collection were using tests, interviews, questionnaires, observation, and documentation study. The analysis technique that used to test the hypotheses is the analysis of parametric statistical difference test. This test will look at different groups of mothers before and after the training conducted. The statistical test used the two side t test with correlated samplesThe results of data processing show that the parenting training model based on spiritual intelligence was effective for improving motherâs behavior in family child care. This is evidenced by the results of testing the hypothesis that there is a significant difference both to aspects of knowledge, skills, attitudes and mothers behavior in family child care before and after the training.The findings of this research show that the parenting training model based on spiritual intelligence effectively helped to improve the knowledge, skills and attitudes of mothers, hence of impact on improving maternal childcare in the family.